A hero for the holidays - Powell, Syndi (Powell, Syndi. Matchmaker at work., 2020)
She's his hero...But they're rescuing each other! When Christopher Fox's house goes up in flames, there's one shining light in the darkness--firefighter Penny Cuthbert. His hero may look like an angel, but the widowed father of two has no time for a romantic distraction. Still, as this strong, bright woman helps him and the kids enjoy the holidays despite all they've lost, he wonders--can love grow out of the ashes?